1998
DOI: 10.1016/s0044-8486(98)00210-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survey on wild and cultured mussels (Mytilus galloprovincialis Lmk) reproductive cycles in the Ria de Vigo (NW Spain)

Abstract: The gonadal development of cultured and wild mussels (Mytilus galloprovincialis) was studied in several localities of the Ria de Vigo (NW Spain) from December 1987 to June 1993. In the mussel populations examined, a stable reproductive pattern, with minor variations, was found. Gametogenesis takes place in late autumn and early winter. In late winter, gonad follicles are full of ripe gametes and some spawns may occur. However, the peak of the spawning season occurs in spring, coinciding with an increase in tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 10 publications
3
23
0
1
Order By: Relevance
“…Mytilus galloprovincialis can release and fertilize gametes during the whole year at intermediate latitudes, although massive spawnings are concentrated between early spring and summer (Snodden & Roberts 1997, Cáceres-Martínez & Figueras 1998b, Suárez et al 2005. Although previous studies in the Ría de Ares-Betanzos described a single spawning event in mid-summer (Villalba 1995), our results showed the largest settlement densities in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…Mytilus galloprovincialis can release and fertilize gametes during the whole year at intermediate latitudes, although massive spawnings are concentrated between early spring and summer (Snodden & Roberts 1997, Cáceres-Martínez & Figueras 1998b, Suárez et al 2005. Although previous studies in the Ría de Ares-Betanzos described a single spawning event in mid-summer (Villalba 1995), our results showed the largest settlement densities in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…In the Mediterranean (southern France and Adriatic coast of northeast Italy) and the Atlantic coast of northwest Spain, gametogenesis occurs even in 1-year-old mussels, starting during autumn and early winter and followed by ripe and spawning seasons during late spring and summer (Cerccherelli & Rossi 1984, Villalba 1995, Cáceres-Martínez & Figueras 1998, Bodin et al 2004. Similarly, on the Pacific coast of Baja California in northwest Mexico, the reproductive season occurs from autumn to early spring (Cáceres-Martínez 2004).…”
Section: Reproductive Cyclementioning
confidence: 99%
“…Wild and cultured mussels of this species have been investigated in terms of their growth, population dynamics, and reproductive cycle, in the Mediterranean (e.g., Ceccherelli & Rossi 1984, Abada-Boudjema & Dauvin 1995, Bodin et al 2004, Lök et al 2007, Peharda et al 2007, Sarà & Pusceddu 2008, Atlantic coast of northwest Spain (Villalba 1995, Cáceres-Martínez & Figueras 1998, west coast of southern Africa (Schurink & Griffiths 1991), and Pacific coast of northwest Mexico (Cáceres-Martínez 2004). These previous works demonstrated that the life-history traits of this species are characterized by a high shell-growth rate, short life span, and an early onset of reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…The black lines are the one-to-one relationships the reproductive seasonality observed in this species, with a peak spawning season in spring coinciding with increases in water temperature and chlorophyll a concentrations. Several spawning events can occur after the first one, generally until summer or late autumn (Cáceres-Martínez & Figueras 1998b). In autumn, a second peak in food availability (Gibbs et al 1992, Gibbs & Vant 1997, Ogilvie et al 2000, MacKenzie & Adamson 2004 may favour the accumulation of reserves for gametogenesis and a subsequent minor spawning event.…”
Section: Spatio-temporal Patternsmentioning
confidence: 99%